conomic training of senior pupils in the process of profile technology education (Pedagogy of Higher and Secondary Education, 2013)
Kulishov V. S. Еconomic training of senior pupils in the process of profile technology education.The article reviews the prerequisites of the economic role and training of senior school pupils in the profile of technological education in accordance with modern trends in society.
Keywords: profile education; economic training; technology education; industrial relations; economic profile training; productive work